2019
DOI: 10.1027/1016-9040/a000349
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices and Recommendations for Digital Interventions to Improve Engagement and Adherence in Chronic Illness Sufferers

Abstract: Abstract. Chronic illnesses cause considerable burden in quality of life, often leading to physical, psychological, and social dysfunctioning of the sufferers and their family. There is a growing need for flexible provision of home-based psychological services to increase reach even for traditionally underserved chronic illness sufferer populations. Digital interventions can fulfill this role and provide a range of psychological services to improve functioning. Despite the potential of digital interventions, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 136 publications
3
89
0
Order By: Relevance
“…Stretched treatment time has been found to prevent attrition amongst youths with chronic pain [28]. A request for a stretched deadline might be a signal of attrition [35]. Although extra time to finish an assignment might be helpful for some, it risks disrupting treatment process and structure.…”
Section: Autonomymentioning
confidence: 99%
See 4 more Smart Citations
“…Stretched treatment time has been found to prevent attrition amongst youths with chronic pain [28]. A request for a stretched deadline might be a signal of attrition [35]. Although extra time to finish an assignment might be helpful for some, it risks disrupting treatment process and structure.…”
Section: Autonomymentioning
confidence: 99%
“…It has been suggested that therapeutic guidance might be necessary to help patients engage in IACT [22]. It has also been suggested that patients with chronic conditions as pain, with comorbid depression and social withdrawal, are less likely to engage in a new treatment approaches, due to previous unsatisfied treatment attempts [35]. The present treatment contained weekly homework assignments which encouraged participants to apply what they had learnt and practice new skills.…”
Section: Treatment Expectationsmentioning
confidence: 99%
See 3 more Smart Citations